Correlation between Follicular Fluid Fatty Acids and Cell-Free Mitochondrial DNA in Women Undergoing Intra-Cytoplasmic Sperm Injections - Alawad, Zainab M.; Al-Omary, Hanan L. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Beta-oxidation of fatty acids takes place in the mitochondria to produce energy. This process is linked to the formation of free radicals. Previous researches propose that some fatty acids may be related to mitochondrial dysfunction, as they induce oxidative stress. Objectives: To examine the correlation between follicular fluid fatty acids and relative cell-free mitochondrial DNA in the follicular fluid in women experiencing intra-cytoplasmic sperm injection (ICSI). Methods: Fifty women subjected to ICSI participated in this cross-sectional research. Follicular fluid samples were obtained during oocyte pick-up. The samples were assessed for fatty acids, utilizing gas chromatography, and for relatively cell-free mitochondrial DNA, real-time polymerase chain reaction (PCR) was used. Results: There was a strong significant positive correlation between follicular fluid margaric acid and follicular fluid relative to cell-free mitochondrial DNA, as the correlation coefficient was 0.869, and the P value was 0.025. In addition, a strong significant inverse correlation was noticed, in women with diminished ovarian reserve, between follicular fluid oleic acid and relative cell-free mitochondrial DNA in the follicular fluid, as indicated by a correlation coefficient = - 0.9 and a P value = 0.037. Conclusion: Margaric acid correlated positively with the relative cell-free mitochondrial DNA, which might reflect mitochondrial dysfunction, due to aggravation of oxidative stress. Whereas, oleic acid, in women with diminished ovarian reserve, correlated negatively with relative cell-free mitochondrial DNA. However, more studies are required in this area of research.